Joint effect of defocus blur and spatial attention. (August 2021) - De Lestrange-Anginieur, E.; Leung, T.W.; Kee, C.S.
Abstract: Defocus blur and spatial attention both act on our ability to see clearly over time. However, it is currently unknown how these two factors interact because studies on spatial resolution only focused on the separate effects of attention and defocus blurs. In this study, eleven participants performed a resolution acuity task along the diagonal 135˚/315˚ with horizontal, at 8˚ eccentricity for clear and blurred Landolt C images under various manipulations of covert endogenous attention. All the conditions were interleaved and viewed binocularly on a visual display. We observed that attention not just improves the resolution of clear stimuli, but also modulates the resolution of defocused stimuli for compensating the loss of resolution caused by retinal blur. Our results show, however, that as the degree of attention decreases, the differences between clear and blurred images largely diminish, thus limiting the benefit of an image quality enhancement. It also appeared that attention tends to enhance the resolution of clear targets more than blurred targets, suggesting potential variations in the gain of vision correction with the level of attention. This demonstrates that the interaction between spatial attention and defocus blur can play a role in the way we see things. In view of these findings, the development of adaptive interventions, which adjust the eye's defocus to attention, may hold promise.